Actualization of Literacy Seminar Program as A Strengthening of Children's Reading Interest in Elementary Schools in Cibodas Village, Lembang District - Putri, Aira Amelia; Azhari, Amalia Fauziah; Kurniawan, Fariz Aziz; Muhardiansyaha, Rifqi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
In the era of Society 5.0, literacy is the ability to read, critically interpret and utilize information effectively. This study evaluates a literacy seminar to foster reading interest among fifth-grade students in Desa Cibodas, Kecamatan Lembang. The seminar aimed to counteract the declining number of active libraries and provide an engaging platform for young learners to develop literacy skills. Using a descriptive qualitative approach, data collection methods included field observations, interviews, and documentation. The study involved 196 students from five elementary schools, reflecting a broad participation level. Findings indicate that the seminar significantly enhanced students' awareness of literacy's importance. The interactive sessions, incorporating storytelling, group reading, and discussions, created an engaging atmosphere that encouraged students to perceive reading as enjoyable rather than an obligation. One of the critical challenges observed was the lack of accessible reading materials due to the closure of village libraries. Despite this, the seminar served as a temporary yet effective intervention, rekindling students' enthusiasm for reading. The discussions emphasized how literacy is fundamental in preparing young learners for an increasingly digital society, where information processing and critical thinking are essential. The seminar's impact extends beyond immediate participation; it lays a foundation for sustainable literacy development, fostering a generation capable of adapting to Society 5.0. This initiative underscores the need for continued community efforts to sustain and expand literacy programs, ensuring long-term educational benefits for Desa Cibodas' students